Laboratory Culture-Based Characterization of the Resting Stage Cells of the Brown-Tide-Causing Pelagophyte, Aureococcus anophagefferens - Zhaopeng Ma; Zhangxi Hu; Yunyan Deng; Lixia Shang; Christophere J. Gobler; Ying Zhong Tang (Journal of Marine Science and Engineering, 2020)
Life history (life cycle) plays a vital role in the ecology of some microalgae; however, the well-known brown-tide-causing pelagophyte Aureococcus anophagefferens has been barely investigated in this regard. Recently, based mainly on detections in marine sediments from China, we proved that this organism has a resting stage. We, therefore, conducted a follow-up study to characterize the resting stage cells (RSCs) of A. anophagefferens using the culture CCMP1984. The RSCs were spherical, larger than the vegetative cells, and smooth in cell surface and contained more aggregated plastid but more vacuolar space than vegetative cells. RSCs contained a conspicuous lipid-enriched red droplet. We found a 9.9-fold decrease in adenosine triphosphate (ATP) content from vegetative cells to RSCs, indicative of a "resting" or dormant physiological state. The RSCs stored for 3 months (at 4 °C in darkness) readily reverted back to vegetative growth within 20 days after being transferred to the conditions for routine culture maintenance. Our results indicate that the RSCs of A. anophagefferens are a dormant state that differs from vegetative cells morphologically and physiologically, and that RSCs likely enable the species to survive unfavorable conditions, seed annual blooms, and facilitate its cosmopolitan distribution that we recently documented.